2023
DOI: 10.1021/acsagscitech.3c00134
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Efficacy and Binding Mode of 1,4-Disubstituted 1,2,3-Triazoles─A New Class of Agricultural Nitrification Inhibitors

Sibel C. Yildirim,
Bethany I. Taggert,
Robert M. Walker
et al.

Abstract: Recently, 1,4-disubstituted 1,2,3-triazoles were reported by us as a new class of nitrification inhibitors, which can outperform the commercial compound 3,4-dimethylpyrazole phosphate (DMPP) in soil incubations. In this work, the mechanism of inhibition of five 1,2,3-triazoles with different substitution patterns was explored using a bacterial assay based on the measurement of nitrite (NO 2 − ) production by pure cell cultures of Nitrosomonas europaea and Nitrosospira multiformis. While polar functional groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 54 publications
(114 reference statements)
0
3
0
Order By: Relevance
“…The cells were subsequently washed thoroughly with NaPB to remove any unbound and bound inhibitor compound, followed by reincubation with NH 4 + for 30 min and measurement of the NO 2 – production. Reversible binding of the NI to AMO would be expected to result in a recovery of the NO 2 – production activity after washing and reincubation, approximately to the level of the uninhibited cells, as we have recently found for DMP, DCD, and a series of 1,4-disubstituted 1,2,3-triazoles. , Control experiments in the absence of inhibitor confirmed that the washing and reincubation protocol did not impact (within error) the NO 2 – production rate of both bacterial strains.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cells were subsequently washed thoroughly with NaPB to remove any unbound and bound inhibitor compound, followed by reincubation with NH 4 + for 30 min and measurement of the NO 2 – production. Reversible binding of the NI to AMO would be expected to result in a recovery of the NO 2 – production activity after washing and reincubation, approximately to the level of the uninhibited cells, as we have recently found for DMP, DCD, and a series of 1,4-disubstituted 1,2,3-triazoles. , Control experiments in the absence of inhibitor confirmed that the washing and reincubation protocol did not impact (within error) the NO 2 – production rate of both bacterial strains.…”
Section: Resultsmentioning
confidence: 99%
“…europaea and N. multiformis, the standard activity and activity recovery assays, the measurements of the O 2 consumption, Michaelis–Menten kinetics, and acute toxicity tests were conducted as previously reported. ,, All bacterial incubations were performed in sodium phosphate buffer (NaPB) with 1% (v/v) DMSO at pH = 7.5 and 30 °C with different inhibitors and concentrations, as indicated. This amount of DMSO, which was required to solubilize the lipophilic inhibitor compounds, is not detrimental to the bacterial cells .…”
Section: Methodsmentioning
confidence: 99%
“…Additional thanks go out to our Editorial Advisory Board members who have provided important guidance and peer reviews and have published their own research this year. The wide range of topics published by our EAB members illustrates their broad expertise ranging from plant science , to soil science and agronomy, sustainable nanomaterials and formulants, ,, pesticide discovery, environmental chemistry, and food safety …”
mentioning
confidence: 99%